#### Answer

49

#### Work Step by Step

To solve this question we know that a=-2, and b=5 and the equation is $(a-b)^{2}$.
$(-2-(5))^{2}$. = $(-2-5)^{2}$ = $(-7)^{2}$. = 49
Square of -7 is 49 as the square of negative number is positive.

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

49

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.